2020
DOI: 10.1101/2020.04.24.20078576
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modeling serological testing to inform relaxation of social distancing for COVID-19 control

Abstract: 15

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 38 publications
6
12
0
1
Order By: Relevance
“…Patterns of IgM and IgG detection align with immunological expectations, as IgM antibodies are typically present during the early phase of the immune response, while IgG antibodies remain detectable for much longer periods ( Xiao et al, 2020 ). We detected IgG and IgM antibodies in nearly all (98–100%) individuals by days 22–23 post-symptom onset, consistent with recent findings ( Kraay et al, 2020 ). While IgG detection remains at this level for at least the range of times in the dataset (60 days for ELISA-Spike), the proportion of IgM-positive samples decreases after roughly 28 days post symptom onset, reaching around 65% by day 60.…”
Section: Discussionsupporting
confidence: 92%
“…Patterns of IgM and IgG detection align with immunological expectations, as IgM antibodies are typically present during the early phase of the immune response, while IgG antibodies remain detectable for much longer periods ( Xiao et al, 2020 ). We detected IgG and IgM antibodies in nearly all (98–100%) individuals by days 22–23 post-symptom onset, consistent with recent findings ( Kraay et al, 2020 ). While IgG detection remains at this level for at least the range of times in the dataset (60 days for ELISA-Spike), the proportion of IgM-positive samples decreases after roughly 28 days post symptom onset, reaching around 65% by day 60.…”
Section: Discussionsupporting
confidence: 92%
“…antibodies are typically present during the early phase of the immune response while IgG antibodies remain detectable for much longer periods (Xiao et al 2020). We detected IgG and IgM antibodies in nearly all (98-100%) individuals by day 22-23 after symptom onset, consistent with recent findings (Kraay et al 2020). While IgG detection remains at this level for at least the remainder of available times in the dataset (60 days), the proportion of IgM-positive samples decreases again, reaching 60-70% by 60 dpo.…”
Section: Patterns Of Igm and Igg Detection Align With Immunological Esupporting
confidence: 92%
“…Assuming such individuals are immune to reinfection, they can be deployed to provide "shield immunity" to preferentially interact with susceptible or infected individuals, thus reducing transmission. 11,28 A model showed that such an immune shielding approach could potentially lead to a reduction in outbreak size. 11 While conceptually sound, it is unclear if such a serological testing-based strategy is viable for college campuses.…”
Section: Serological Testing For Antibodies and "Immune Shield" Strategymentioning
confidence: 99%
“…31,33 If an individual is placed into an "immune shield" position despite not actually being immune, this could lead to an increase in transmission. 28 Fourth, preliminary results of seroprevalence studies suggest that immune individuals will be in short supply. A meta-analysis of multiple seroprevalence studies using Bayesian hierarchical models, 34 found that seroprevalence is low among the populations investigated, with 2-6% in Los Angeles County, California, 35 0-2% in Santa Clara County, California, 36 1.6-2.6% in San Miguel County, Colorado, and 15-41% in Chelsea, Massachusetts.…”
Section: Serological Testing For Antibodies and "Immune Shield" Strategymentioning
confidence: 99%